Financial distress analysis at Bank Muamalat for 2016-2020 - Mauludi, Silvie; Mardani, Dede Aji (Journal of Islamic Economics Management and Business (JIEMB), 2022)
The monetary crisis that hit Southeast Asia has affected the financial condition of banks –including Islamic banks– so there is a potential for financial distress. The same thing was experienced by Bank Muamalat as the first sharia bank in Indonesia. This study aims to analyze the effect of the working capital ratio on total assets, retained earnings on total assets, profit before interest tax on total assets, and a book value of equity on the total book value of liabilities simultaneously on financial distress at Bank Muamalat. The method used is quantitative by using an analytical tool in the form of SPSS with a sample of Bank Muamalat. The results of this study indicate that Islamic banks on the ratio variables of WCTA, RETA, EBITTA and BVETL simultaneously have a significant effect on financial distress. This means that the ability of liquidity, profitability and solvency, as reflected in Altman’s four financial ratios if tested multivariate, will produce a reasonably accurate financial distress prediction from the influence of the four ratio variables. However, if tested univariately, some ratios will be dominant. Other ratios will become supporting ratios and state that 32-month banks are in category 1 (grey zone) and 28 months are in category 0 (stressed zone). This research implies that if the four components are combined in the bank test, there will be financial distress. To avoid financial distress, all components must be maintained both in terms of operations, resources and financial condition (distress zone).Keywords: financial distress; Bank Muamalat; monetary crisis; WCTA; RETA; EBITTA.